HUBUNGAN KEKUATAN OTOT LENGAN, KEKUATAN GENGGAMAN TANGAN TERHADAP KECEPATAN REAKSI MAHSISWA PJKR 2018 PENGEMAR GAME ONLINE - erick prayogo walton; OKTARINA OKTARINA (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2020)
The background of this research was supported that there was not yet known about the effects of online games for PJKR students in the academic year of 2018. This study was proposed to determine the relationship between arm-muscle strength and hand-grip strength toward the reaction speed of online game players of PJKR students at STKIP Muhammadiyah Bangka Belitung. This study used a quantitative approach with the correlational method. The sample was 40 students by using purposive sampling. The analysis data in this research used correlational product-moment technique, the data also measured by using pre-requisite tests, there is a normality test, linearity test, and hypothesis test. The data were analyzed using SPSS 16 at the significance level of 5%. Related to the measurement test using SPSS 16, the results of this research show that variable X1 and Y are sig 0.472; while variable X2 and Y are sig 0.273. And based on the testing of multiple correlational computations between variable X1, X2, and Y, there is sig 0.549. All the scores are higher than 0.05, or sig > 0.05, so it can be concluded that there is no positive correlation between arm-muscle strength and hand-grip strength toward the reaction speed of online game players of PJKR students at STKIP Muhammadiyah Bangka Belitung.